A protocol for genetic analysis at different stages of the nuclear division cycle in Neurospora crassa - Kotaro Tsukada; Shin Hatakeyama; Shuuitsu Tanaka (Fungal Genetics Reports, 2023)
The filamentous fungus Neurospora crassa is an organism that contains multiple nuclei in the asexual conidia and hyphae. Since the nuclei of dormant conidia are arrested at various points in the nuclear division cycle, it has been difficult to analyze drug sensitivity at the specific point of the cycle in N. crassa. In this study, we have established a useful method for analysis at different stages of the nuclear division cycle in N. crassa. This assay will be a reference for researchers to use the synchronized culture in other diverse analyses.
Keywords: Neurospora crassa; Cell cycle; Picolinic acid; DNA replication; DNA damage; DNA repair